2019
DOI: 10.1111/anae.14541
|View full text |Cite
|
Sign up to set email alerts
|

A physiological study to determine the mechanism of carbon dioxide clearance during apnoea when using transnasal humidified rapid insufflation ventilatory exchange (THRIVE)

Abstract: Summary Clinical observations suggest that compared with standard apnoeic oxygenation, transnasal humidified rapid‐insufflation ventilatory exchange using high‐flow nasal oxygenation reduces the rate of carbon dioxide accumulation in patients who are anaesthetised and apnoeic. This suggests that active gas exchange takes place, but the mechanisms by which it may occur have not been described. We used three laboratory airway models to investigate mechanisms of carbon dioxide clearance in apnoeic patients. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 47 publications
4
93
4
Order By: Relevance
“…A paper in this issue of the journal proposes a novel additional mechanism that may be responsible .…”
Section: High‐flow Nasal Oxygen: Novel Mechanismsmentioning
confidence: 99%
“…A paper in this issue of the journal proposes a novel additional mechanism that may be responsible .…”
Section: High‐flow Nasal Oxygen: Novel Mechanismsmentioning
confidence: 99%
“…Subsequently, case series by other groups , randomised trials and widespread international experience have confirmed beyond doubt that this is a highly effective approach to apnoeic oxygenation. However, the data surrounding the concept of carbon dioxide clearance during apnoea with high‐flow nasal oxygen is more limited, raising the possibility that recent modelling and simulation exercises are premature, and that appropriately conducted randomised trials in adults are still required. It is thus timely to re‐examine the strengths and weaknesses of the carbon dioxide data during apnoea, in contrast to the more established benefits associated with high‐flow nasal oxygen.…”
mentioning
confidence: 99%
“…The rate of rise of carbon dioxide using THRIVE was found to be 1.2 mm Hg/min, compared to classic apnoeic oxygenation technique with rate of rise of carbon dioxide of 2.6‐3.3 mm Hg/min. This carbon dioxide clearance mechanism has been suggested to be dependent on flow rate and affected by cardiogenic oscillations . These initial studies have subsequently revolutionized airway management in adult anesthesia providing a safer oxygenation technique allowing a less hurried approach to difficult airways.…”
Section: Physiology Of Apnoeic Oxygenationmentioning
confidence: 99%